Analisis Tindak Tutur dalam Film The Road (2009) - Ridha, Muhammad Rasyid; Pratiwi, Anne (English Study Program, Faculty of Humanities, Universitas Andalas, Padang, 2025)
This paper explores the use of speech acts in the movie, The Road. Speech acts are actions that are performed by human utterances. Speech acts include things like requesting, apologizing, promising, and other utterances that humans do that resemble an action. Based on Searle’s classification of speech acts, there are five classes of speech acts: assertive, directive, expressive, commissive and declaration. The paper analyzed speech acts in the film’s dialogue and classify them into Searle's speech acts theory. The paper shows most of the speech acts categories are included in The Road’s dialogue except for declaration. The analysis shows that the movie includes most of these types: characters make statements and give information (assertive), give commands, warning, ask questions (Directive), express emotions and feelings (expressive), and make promises, threats and vow (commissive). The absence of declaration in the movie happens because the setting of the movie is in a post-apocalyptic world where there is no authority figure that can make change to the world, making the speech act of declaration is almost impossible. Overall, the study reveals the function and the importance of speech acts in movie dialogue.